1988
DOI: 10.1111/j.1600-0714.1988.tb01506.x
|View full text |Cite
|
Sign up to set email alerts
|

Early invasion of squamous cell carcinoma of the tongue: of 31 cases

Abstract: Early invasion of squatnous cell carcinoma of the tongue: pathology of 31 cases. J Oral pathol 1988: 17: 49-54.Thirty-one cases of early invasive squamous cell carcinotna (SCC) of the lateral border of the tongue were analyzed histologically; 9 were also serially sectioned. Three-dimensional reconstruction graphics showed that tnost of the invasive islands were connected with the adjacent epithelium, in spite of the apparent separation of islands on one histological section. Deep elongation, branching-off of r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1993
1993
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…The main feature of de-differentiation in our material was the presence of thin, irregular, widely separated or even fully isolated tumor-cell strands, contrasting sharply with the compact, closely packed groups found in S.C. tumors (Gabbert, 1985). On the basis of serial sections, several investigators have found that most of the seemingly isolated cell groups in the periphery of invasive tumors are still connected to the main tumor mass (Carr et al, 1989;Hasega and Kayano, 1988;Sakuma et al, 1985;Seski and Schmid, 1982). This seems unlikely in our material, given the very large distance frequently observed between small tumor-cell groups and the main tumor mass.…”
Section: Discussionmentioning
confidence: 84%
“…The main feature of de-differentiation in our material was the presence of thin, irregular, widely separated or even fully isolated tumor-cell strands, contrasting sharply with the compact, closely packed groups found in S.C. tumors (Gabbert, 1985). On the basis of serial sections, several investigators have found that most of the seemingly isolated cell groups in the periphery of invasive tumors are still connected to the main tumor mass (Carr et al, 1989;Hasega and Kayano, 1988;Sakuma et al, 1985;Seski and Schmid, 1982). This seems unlikely in our material, given the very large distance frequently observed between small tumor-cell groups and the main tumor mass.…”
Section: Discussionmentioning
confidence: 84%